Research on Tripartite Evolutionary Game and Stability Analysis Considering Multi-Agent Cooperation Between Pumped Storage Station and Wind-Solar Power Stations - DUAN Shaowei, CAI Ye, TANG Xiafei, TANG Liang, TAN Yudong (Dianli jianshe)
Against the background of the goal of “carbon peak and carbon neutrality”， it will be inevitable to form multi-agent cooperative alliance between pumped storage stations， wind power stations， and photovoltaic power stations driven by interests. However， the form of multi-agent cooperative alliance is not static and may break down during the evolution process. Evolutionary games are commonly used to study the cooperative operation of entities in the electricity market， so it can be used to study the long-term stability of cooperative alliances. However， as a non completely rational game method， it ignores the complexity and randomness of the game process. This article constructed a benefit coordination model based on evolutionary game theory， optimized the output of each agents， and solves the evolutionary game benefit matrix. Then， this article constructed tripartite determine evolutionary game model and stochastic evolutionary game model of wind power stations， solar power stations and pumped storage stations， revealing the mechanism of the formation and rupture of multi-agent cooperative alliance. Based on actual data from a certain province， this article concludes that it is feasible for pumped storage stations to participate as entities in the cooperative alliance in the future， and the cooperative alliance can be divided into initial stage， development stage， and rupture stage according to the proportion of new energy installed capacity； Under the influence of random interference factors， there is a possibility for solar power stations to withdraw from the alliance in advance； The stable cooperative alliance has shown excellent performance in ensuring the consumption of new energy. The above conclusions provide theoretical support for the participation of pumped storage power stations in profit oriented cooperative alliances， and provide direction for power grid companies to maintain the stability of cooperative alliances.